EFEKTIVITAS RESTORATIVE JUSTICE PERSPEKTIF JINAYAH: Studi Penerapan Perpol Nomor 8 Tahun 2021 Tentang Di Polresta Surakarta - Khayaatin, Rahma; Widodo , Aris (MAQASHID, 2025)
Abstract:  Restorative justice is an alternative approach to resolving criminal acts without punishment that has been implemented in Indonesia since 2021 at the police level. The purpose of this interview is to obtain more in-depth information about how restorative justice is implemented, including experiences, opinions, and obstacles encountered, as well as to obtain data and information related to the practice of restorative justice at the Surakarta Police Headquarters. The research method used in this study is qualitative research, with a normative and empirical approach. This study uses secondary data as its main source. This study uses interview techniques to collect data.  The data analysis technique used in this study is the qualitative approach according to Miles and Huberman, which consists of three main stages, namely data simplification (reduction), data presentation, and conclusion drawing. Based on the results of the study, the implementation of Police Regulation Number 8 of 2021 concerning Restorative Justice at the Surakarta Police Headquarters is considered ineffective. To ensure equitable and fair implementation for all levels of society, Police Regulation No. 8 of 2021 should be repealed and replaced with a Law on Restorative Justice that adopts the principle of diyat in Islam. However, the formulation of a Law on Restorative Justice that adopts the principle of diyat in Islam in Indonesia needs to be done carefully, inclusively, and contextually so that the values of justice, benefit, and forgiveness can be accepted by the entire community and not considered as a practice of the majority religion.